THROUGH OUR LENS: EXPLORING CULTURAL ADAPTATION OF MIRACLE IN CELL NO. 7 KOREAN FILM AND ITS INDONESIAN VERSION - Fitriana, Annisa; Fiaunillah, Fariha Najda; Anggraeni, Changmia; Pitaloka, Wistiani Putri Diah; Anahita, Nuhla; Raharjo, Jasmine Aulia; Wijayanti, Estu; Sari, Ayu Puspita (CrossOver, 2024)
This research enriches the rare discussion of adaptation especially related to representation of local culture in cross-border film adaptations. While many studies focus on narrative and thematic changes, in-depth analysis of how local culture, such as social values, traditions, and Indonesian identity are adapted in the story is still minimal. This research explores how Korean cultural elements in the film Miracle in Cell No. 7 are adapted into Indonesian culture and are adjusted to Indonesian values in the adaptation version. Using the theory of transstylization by Genette (1997) and the theory of seven cultural elements by Koentjaraningrat (1986), it was found that five cultural elements underwent changes, namely language, religion, knowledge system, living equipment, and livelihood system. This is not only because Korea and Indonesia basically have different culture but also influenced by the different religious landscape. This research contributes to the understanding of how Indonesian local culture is integrated in movie adaptations without changing the core of the original story.